Online Learning Implementation during the Covid-19 Pandemic: Teachers’ Perception and Students’ Responses - Ni Made Ratminingsih; Made Hery Santosa; Luh Diah Surya Adnyani; I Ketut Trika Adi Ana (Jurnal Pendidikan Indonesia, 2022)
Technology plays a vital role in education, most currently due to the Covid-19 pandemic, forcing educators to work and students to study from home. This study aims to analyses teachers' perception and students' responses toward the online learning implementation which have undergone for more than one year. The study utilized mixed-method research of quantitative and qualitative, which was conducted by a survey and interview. It involved 37 teachers comprising the full-time and part-time teachers and eight representative students from 4-year levels. There were two instruments used to collect the data, namely questionnaire and interview guide. The findings were analyzed descriptively. First, the results from the questionnaires were presented quantitatively by calculating the percentage and then determined by using theoretical ideal reference assessment. The result of this study proved that most teachers generally had a good perception of the implementation of online learning. Additionally, the students mainly had good responses toward the implementation of online learning. Thus, in the year ahead, this kind of learning is becoming an appropriate model that needs to be implemented maximally with better treatment, especially in a virtual meeting via more synchronous platforms.